Fungicides in crop protection: Second edition - Oliver, Richard; Hewitt, H. (CABI International, 2014)
© R.P. Oliver and H.G. Hewitt 2014. All rights reserved. Plant pathogenic fungi cause devastating damage to crop production worldwide. The growing global population necessitates reduced crop losses to improve food security, and the control of fungal plant pathogens is vital to help maintain food production. Providing a concise and balanced review of fungicides used in crop protection, this book describes the science of fungicide use, selection and resistance within the context of farming situations. Major updates and additions reflecting the emergence of two new classes of fungicides (strobilurins and SDHI) and the increased incidence of fungicide resistance are included in this new edition, which also discusses legislative requirements to reduce fungicide applications, and current trends in fungicide use.